Bias Awal Penciptaan Perempuan Dalam Tafsir Alquran (Perspektif Pendekatan Tekstual dan Kontekstual) - Agus Imam Kharomen (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This writing proves that form of textual and contextual interpretation are not caused by period/ time (classic, modern, contemporary), but they are not caused by interpreter’s method and approach. This research also disagrees many opinions included orientalist who always assesses classical interpreter produces textual interpretation. This research is bibliographical (Library Research) with interpretation (tafsir) study object from classical interpreter Al-Tarbari (passed away 923) al-Zamakhsyarî (1144), Ibnu ‘Atiyyah (1159), al-Qurtubî (1273), Abî Hayyân (1344), mufasir modern al-Syinqtî (1973) and Wahbah al-Zuhailî (born 1932), al-Marâghî (1952), al-Qâsimî (1914), Râsyid Ridâ (1935), al-Sya‘râwî (1998) and contemporary M. QuraishShihab (born 1944). In process, this research uses method of analytical descriptive by approach content analysis and comparative with analysis of Abdullah Saeed theory about category of textual and contextual approach.